EVALUATION OF THE QUALITY OF FOREIGN LANGUAGE TEACHING IN TERMS OF MULTICULTURAL EDUCATION - Sharkova, Svitlana (PSYCHOLOGICAL JOURNAL, 2018)
Issues regarding the quality of foreign language teaching and the results of foreign language acquisition have been analyzed. It has been suggested to accept multicultural student group as a linguistic environment for foreign language acquisition when communication is achieved through personal interaction by means of the language which is studied. It has been shown that the language teaching needs to broaden its horizons beyond the narrowly linguistic. A starting point for any intercultural training, much like interpersonal learning, is to consider student’s own culture and how other people perceive it. Practical suggestions on how teachers can create activities to develop those skills for second language acquisition have been offered. The range of activities that increase students’ sociocultural awareness have been introduced. The effect of intercultural-sensitivity training has been proved. According to the survey the students from control groups pointed out that their best developed skill in the end of the course is “listening” and the worst developed skill is “teamwork”. At the same time the opposite tendencies were reflected in estimations of the participants from experimental groups. The role of other language skills (“speaking”, “better comprehension of the material”) has been also evaluated. It has been revealed that in experimental groups there are positive changes in motivation of students. All results of the study have been measured with mathematical methods. The analysis of pre-test and post-test data during Grammar check has revealed no significant changes in control groups. However, in experimental groups Grammar Test score has changed from 12.26 to 15.76 in the end of the course which is considered to be significant due to the values for Student’s t-distributions. In terms of pilot research study it has been discovered that the implementation of such intercultural-sensitivity training is not that beneficial when the group is comprised just of Ukrainian or Russian speaking students, unless other foreigners are invited to a range of classes. Forming multicultural groups with representatives who speak different languages has become one of highly influential factors. In this case, new linguistic environment is created to exchange information. Meanwhile, the further development of English language teaching strategies should be encouraged, especially in terms of multicultural education.